(untitled) (Research Journal of Padmakanya Multiple Campus, 2023)
Four species of the family Ranunculaceae were collected from Shivapuri Nagarjun National Park (SNNP). These were Aconitum ferox Wall ex Ser, Clematis smilacifolia Wall, Ranunculus scleratus L. and Thallictrum foliolosum DC. Among these Aconitum ferox is threatened plant and are widely collected for medicinal purpose. The plant is used for curing many diseases. Nepal is rich in biodiversity and it harbors 2% of the world’s flowering plants and it boasts around 6200 species. Floral diversity is quite high in SNNP due to its location, altitudinal and climatic variations. However its detailed study is not undertaken till now. Human survival primarily depends upon the plant resources. Plants and plant product form an integral part of our life and it is extremely difficult to imagine the survival of human without it. The area shows climatic variation from subtropical to lower temperate. Indigenous knowledge and traditional practice about the use of plants of SNNP has not been documented.